Synthesis of Antenna Arrays and Parasitic Antenna Arrays with Mutual Couplings. (4th April 2012) - Thevenot, M.; Menudier, C.; El Sayed Ahmad, A.; Zakka El Nashef, G.; Fezai, F.; Abdallah, Y.; Arnaud, E.; Torres, F.; Monediere, T.
Abstract : A synthesis method to design multielement antennas with couplings is presented. The main objective is to perform a rigorous determination of the electromagnetic characteristics involved in the design, especially with arrays of moderate sizes. The aim is to conceive jointly and efficiently the antenna and the circuits to connect (feed distribution network, power amplifiers, reactive loads, etc.). The subsequent objective is to improve the understanding and capabilities of strongly coupled antennas. As a whole, the synthesis procedure is then applied to different antenna architectures in order to show its efficiency and versatility. A focus on some antenna concepts where the management of couplings is a key factor to improve the performances is presented. After describing the synthesis procedure, the first category of coupled multielement antenna studied concerns radiating arrays in linear or circular polarization. A design including couplings effects on an active array is also presented. Then, the method is applied to parasitic antenna arrays and a specific investigation on reflectarray antenna is performed as they can be considered as a particular case of parasitic arrays.